The evolution of Anti-Money Laundering and Anti-Terrorism Financing (AML/ATF) regime in Malaysia / Zaiton Hamin ... [et al.] - Hamin, Zaiton; Othman, Mohd Bahrin; Kamaruddin, Saslina (2014)
Money laundering is regarded as the world’s third largest industry, after international oil trade and foreign exchange. In 2009, the United Nations Office on Drugs and Crime (UNODC) has estimated that the total amount of money being laundered has reached USD 1.6 trillion. The extent of the problem has led to many legal and regulatory efforts at international and national levels to curb the crime. In the Malaysian context, the government has taken preventive measures in combating money laundering by introducing the Anti-Money Laundering Act in July 2001 and its amendment in 2003. In view of the above, this paper attempts to chart the evolution of AML/ATF law in Malaysia since its inception in 2001 and to examine the extent of its compliance with the International Recommendations issued by the Financial Action Task Force (FATF). The authors contend that the creation of legal and regulatory framework in governing money laundering and terrorism financing in many jurisdictions around the world, including Malaysia, is in accord with international standards. Despite such modalities and global governance, such crimes remain significant threats to the national and global financial systems. This paper employed a doctrinal legal analysis and secondary data of which the Anti-Money Laundering and Terrorism Financing Act 2001 (AMLATFA) is the primary source. The secondary sources for this research include decided cases, articles in academic journals, books and online databases.